High-brightness quantum dot fluorescent microsphere and preparation method thereof based on base catalysis strategy
Through a method based on the alkali catalytic strategy, high-bright quantum dot fluorescent microspheres were prepared, which solved the problem of degradation of fluorescence properties during the oil-phase quantum dot coating silica, and achieved efficient preparation of fluorescence microspheres, maintaining the optical properties and stability of quantum dots.
Patent Information
- Application Number
- CN202510003411.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-02
AI Technical Summary
The prior art in the process of coating silica with oil-phase quantum dots, resulting in a decrease in fluorescence properties and a significant reduction in fluorescence quantum yield.
Using a base catalytic strategy method, high-bright quantum dot fluorescent microspheres were prepared by preparing thiol-modified dendritic mesoporous silica microspheres and quantum dot assembly, 3-mercaptopropyltriethoxysilane was used to perform organosilane modification in a non-polar organic solvent, and a silica shell was grown on the surface of the organosilane-modified dendritic silica/quantum dot assembly to obtain high-bright quantum dot fluorescent microspheres.
The fluorescence quenching of oil-phase quantum dots during the coating of silica is avoided, and the excellent optical properties of quantum dots are maintained, which improves the stability and fluorescent quantum yield of quantum dot microspheres.
Smart Images

Figure CN119799317A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of quantum dot fluorescent materials, and in particular to a high-brightness quantum dot fluorescent microsphere and a preparation method thereof based on a base catalysis strategy. Background Art
[0002] Quantum dots have excellent optical properties such as high fluorescence emission efficiency, continuously adjustable fluorescence emission spectrum, wide absorption spectrum, narrow emission spectrum, and resistance to photobleaching. In recent years, they have become a hot topic of widespread concern in the biomedical field.
[0003] At present, quantum dots with high luminescence efficiency, narrow half-peak width, single exponential fluorescence decay kinetics and flicker-free luminescence are usually synthesized in organic phases, and their surfaces are coated with hydrophobic organic ligands such as fatty acids and fatty amines, which limits their direct application in biological systems. How to modify the surface of quantum dots, make them water-soluble and keep their excellent optical properties is the key to their biological application.
[0004] It is reported that the oil phase quantum dots wrapped with silica can make the quantum dots water-soluble, which can be divided into two types. The first is the sol-gel process ( Method), wherein quantum dots are used as seed liquid, a mixture of ethanol and water is used as a reaction medium, and silica is grown under the catalytic action of ammonia water, and the silica spheres finally obtained contain one or more quantum dots. The size distribution and dispersibility of the quantum dots / silica particles prepared by this method are relatively poor (for example, Ma Y, Li Y, Ma S, et al. Highly bright water-soluble silica coated quantum dots with excellent stability [J]. Journal of Materials Chemistry B, 2014, 2 (31): 5043-5051.). The second method is an "oil-in-water" reverse microemulsion system, in which hydrolyzed tetraethyl silicate will exchange ligands with hydrophobic ligands on the surface of quantum dots, so that the quantum dots are transferred to hydrophilic micelles, and ammonia water is used as a silane hydrolysis catalyst to achieve the growth of silica (for example, the Chinese patent with publication number CN 110129025 A discloses a method for preparing silica-encapsulated quantum dots).
[0005] Unfortunately, both of the above methods require the use of polar reagents such as alcohols, water, and ammonia, which inevitably deteriorates the optical properties of oil-phase quantum dots and greatly reduces the fluorescence quantum yield.
[0006] Therefore, there is an urgent need for a new method for preparing quantum dot fluorescent nanospheres that avoids the reduction of fluorescence properties during the process of oil-phase quantum dots encapsulating silica. Summary of the invention
[0007] The invention provides a high-brightness quantum dot fluorescent microsphere and a preparation method thereof based on a base catalysis strategy. The preparation method of the invention avoids the fluorescence quenching of the oil phase quantum dots during the process of coating with silicon dioxide.
[0008] The technical solution of the present invention is as follows:
[0009] A method for preparing high-brightness quantum dot fluorescent microspheres based on a base catalysis strategy comprises the following steps:
[0010] (1) Preparation of thiol-modified dendritic mesoporous silica microspheres;
[0011] (2) assembling the thiol-modified dendritic mesoporous silica microspheres with quantum dots to obtain a dendritic silica / quantum dot assembly;
[0012] (3) adding 3-mercaptopropyltriethoxysilane to the dendritic silica / quantum dot assembly, and using an organic base as a base catalyst in a non-polar organic solvent to modify the dendritic silica / quantum dot assembly with an organic silane;
[0013] (4) Through Methods A silica shell was grown on the surface of organosilane-modified dendritic silica / quantum dot assemblies to obtain high-brightness quantum dot fluorescent microspheres.
[0014] The invention utilizes the coordination effect of metal and sulfur group to realize the assembly of oil phase quantum dots on dendritic mesoporous silica microsphere template; then, 3-mercaptopropyltriethoxysilane (MPTMS) is used as silane reagent, and organic base is used as base catalyst in non-polar organic solvent to obtain organosilane modified dendritic silica / quantum dot composite material, so as to realize the transformation of quantum dots from lipophilic to hydrophilic; finally, The method grows a silica shell on the surface of an organosilane-modified dendritic silica / quantum dot assembly. The preparation method of the present invention avoids the fluorescence quenching of oil-phase quantum dots during the silica coating process, and the chemically inert silica shell acts as a barrier to isolate the influence of external factors on the optical properties of quantum dots, thereby greatly improving the stability of quantum dot microspheres.
[0015] Preferably, step (1) comprises: preparing dendritic mesoporous silica by a template method, and then modifying the surface of the dendritic mesoporous silica with thiol groups to obtain thiol-modified dendritic mesoporous silica microspheres.
[0016] Further preferably, step (1) comprises:
[0017] (1-1) Using hexadecyltrimethylammonium bromide (CTAB) as a template, sodium salicylate (NaSaI) as a structure directing agent, triethanolamine (TEA) as a catalyst, and water as a solvent, stirring the reaction at 50-100°C for 0.5-2h, adding a silicon source and continuing to stir the reaction for 2-3.5h to obtain dendritic mesoporous silica;
[0018] (1-2) Add 3-mercaptopropyltriethoxysilane (MPTMS) and an alkaline solution to the dendritic mesoporous silica and stir the mixture to react at room temperature to obtain thiol-modified dendritic mesoporous silica microspheres.
[0019] In step (1-1), a series of reaction parameters such as the amount of raw materials fed and the reaction time are adjusted to obtain dendritic silicon dioxide of different sizes.
[0020] Preferably, in step (1-1), the mass ratio of hexadecyltrimethylammonium bromide, sodium salicylate and triethanolamine is 1:0.1-1.1:0.1-0.2.
[0021] Preferably, the particle size of the thiol-modified dendritic mesoporous silica microspheres is 100-500 nm.
[0022] Preferably, in step (2), the mass ratio of the thiol-modified dendritic mesoporous silica microspheres to the quantum dots is 1:1-2.
[0023] Preferably, step (2) comprises: adding oil-soluble quantum dots to the dispersion of thiol-modified dendritic mesoporous silica microspheres, and ultrasonicating for 5-30 minutes to obtain a dendritic silica / quantum dot assembly.
[0024] Preferably, the quantum dots are CdSe / CdS / ZnS, CdZnSeS / ZnS, CdSe / CdZnS, InP / ZnSe / ZnS, CuInS 2 / ZnS; the ligand on the surface of the quantum dots is at least one of oleic acid, decadecanoic acid, stearic acid, and n-dodecyl mercaptan.
[0025] Preferably, step (3) comprises: adding 3-mercaptopropyltriethoxysilane to the dendritic silica / quantum dot assembly, using an organic base as a base catalyst in a non-polar organic solvent, stirring the reaction at room temperature for 60-120 minutes to obtain an organosilane-modified dendritic silica / quantum dot assembly.
[0026] Further preferably, in step (3), the non-polar organic solvent is at least one of toluene, chloroform, octane and cyclohexane.
[0027] Further preferably, in step (3), the organic base is at least one of tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide and hexamethonium hydroxide.
[0028] Further preferably, in step (3), the volume ratio of 3-mercaptopropyltriethoxysilane to the organic base is 1:0.3-1.
[0029] Preferably, step (4) comprises: adding a silicon source to a dispersion of the organosilane-modified dendritic silica / quantum dot assembly, and reacting with stirring at room temperature for 18-36 hours under the action of an alkali catalyst to obtain high-brightness quantum dot fluorescent microspheres.
[0030] Further preferably, in step (4), the base catalyst is at least one of ammonia water, dimethylamine, ethylenediamine, triethylamine, and tetramethylammonium hydroxide.
[0031] Further preferably, in step (4), the base catalyst is 25-28 wt % ammonia water; the silicon source is tetraethyl silicate; and the volume ratio of the silicon source to the base catalyst is 1:1-3.
[0032] The present invention also provides a high-brightness quantum dot fluorescent microsphere prepared by the above preparation method.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] The present invention uses 3-mercaptopropyltriethoxysilane to modify the surface of oil-phase quantum dots, uses an organic base as a catalyst, and uses a non-polar organic solvent as a solvent. Without using any polar solvent, the transformation of the oil-phase quantum dots from lipophilic to hydrophilic is achieved, and the excellent optical properties of the oil-phase quantum dots are completely retained. The obtained quantum dot microspheres have a high fluorescence quantum yield. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 Schematic diagram of the preparation process of high-brightness quantum dot composite microspheres.
[0036] Figure 2 These are transmission electron micrographs of CdSe / CdS / ZnS quantum dots (a), 250 nm dendritic mesoporous silica (b), dendritic mesoporous silica / CdSe / CdS / ZnS quantum dots (c), and dendritic mesoporous silica / CdSe / CdS / ZnS quantum dots / silica composite microspheres (d) in Example 1. The inset in (a) is a high-resolution transmission electron micrograph of quantum dots.
[0037] Figure 3 This is a comparison chart of the fluorescence intensity before and after the oil phase quantum dots are wrapped with silica in Example 1.
[0038] Figure 4 This is a comparison chart of the fluorescence kinetic decay curves before and after the oil phase quantum dots are wrapped with silica in Example 1.
[0039] Figure 5 The relative fluorescence intensity of the quantum dot composite microspheres in Example 1 at different NaCl concentrations.
[0040] Figure 6 is the relative fluorescence intensity of the quantum dot composite microspheres in Example 1 at different pH values.
[0041] Figure 7 The relative fluorescence intensity of the quantum dot composite microspheres in Example 1 after storage for 30 days. DETAILED DESCRIPTION
[0042] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be pointed out that the embodiments described below are intended to facilitate the understanding of the present invention and do not have any limiting effect on the present invention.
[0043] The preparation process of the high brightness quantum dot composite microspheres of the present invention is as follows: Figure 1 shown.
[0044] Example 1
[0045] (1) Dendritic mesoporous silica (dSiO) with a size of 250 nm 2 ) Synthesis of carrier
[0046] Weigh 68 mg of triethanolamine (TEA) and dissolve it in 25 mL of deionized water, stir at 80 ° C for 30 min, then add 380 mg of hexadecyltrimethylammonium bromide (CTAB) and 168 mg of sodium salicylate (NaSaI), and continue to react at 80 ° C for 1 h. Then add 4 mL of tetraethyl silicate (TEOS) to the solution, continue to react at 80 ° C for 2 h, and collect the precipitate by centrifugation with ethanol after the reaction. Use 100 mL of a mixed solution of hydrochloric acid / methanol (volume ratio of 1:1) for purification, stir at 60 ° C for 6 h, repeat this step three times to remove excess organic template hexadecyltrimethylammonium bromide, and finally centrifuge with ethanol for 3 times, centrifuge at 9000 rpm for 3 min, and disperse again in 100 mL of ethanol to prepare dendritic silica spheres with a size of 250 nm.
[0047] (2) Surface thiolation treatment of dendritic mesoporous silica
[0048] 1 mL of 3-mercaptopropyltriethoxysilane (MPTMS) and 2.5 mL of ammonia solution (mass concentration of 25-28 wt%) were added to the ethanol solution of the dendritic mesoporous silica prepared in step (1), and the mixture was stirred at room temperature for 15 h. The mixture was centrifuged three times with ethanol and centrifuged at 8000 rpm for 5 min. The collected precipitate was dispersed in 50 mL of ethanol again to obtain thiol-functionalized dendritic silica (dSiO 2 -SH) template.
[0049] (3) Dendritic Silica / Quantum Dots (dSiO 2 Preparation of nanostructured QDs (nano / QDs) assemblies
[0050] The ethanol solution of the thiolated silica template in step (2) was centrifuged at 8000 rpm for 5 min, the supernatant was discarded, the precipitate was dried and accurately weighed to 10 mg, 1 mL of purified CdSe / CdS / ZnS quantum dot chloroform solution (the purification agent was a mixed solution of chloroform, acetone and methanol, the volume ratio was 1:1:1, and the quantum dot concentration was 15 mg / mL) was added, and ultrasonication was performed for 10 min. In this step, CdSe / CdS / ZnS quantum dots were assembled in the pores of dendritic silica. Centrifuged at 10000 rpm for 5 min, the precipitate was washed with chloroform to remove free quantum dots, and dendritic silica / quantum dots (dSiO 2 / QDs) assembly was dispersed in 5 mL of toluene solution for later use.
[0051] (4) Preparation of dendritic silica / quantum dots / silica (SQS) fluorescent nanospheres
[0052] dSiO 2 The organosilane-modified dendritic silica / quantum dots (dSiO 2 / QDs / MPTMS). The dSiO 2 / QDs / MPTMS was centrifuged and the precipitate was washed again with ethanol. Methods To grow a silica shell, the above precipitate was dispersed in 20 mL of ethanol and 100 μL of tetraethyl orthosilicate, 200 μL of ammonia water, and 200 μL of water were added, and stirred at room temperature for 18 h. The solution was centrifuged and washed with ethanol three times to obtain high-brightness dendritic silica / quantum dots / silica fluorescent nanospheres.
[0053] Depend on Figure 2It can be seen from the transmission electron microscope pictures that the quantum dots, the dendritic silica carrier, the dendritic silica / quantum dot assembly, and the dendritic silica / quantum dot / silica composite microspheres in Example 1 have good monodispersity and uniform particles.
[0054] The dendritic silica / quantum dots / silicon dioxide nanospheres prepared in this embodiment have excellent optical properties and a quantum yield of more than 95%. Figure 3 It can be seen that there is no obvious change in the peak position, half-peak width and intensity of the fluorescence spectrum of the quantum dot microspheres before and after being wrapped with silica. Figure 4 This indicates that the fluorescence kinetic decay curves of the quantum dot microspheres before and after silica encapsulation can still be fitted with a single exponential function, and no new non-radiative recombination channels are generated, indicating that the dendritic silica / quantum dot / silica nanospheres prepared in this example maintain good optical properties.
[0055] The dendritic silica / quantum dots / silicon dioxide nanospheres prepared in this embodiment have ultra-stable optical properties. Figure 5 It can be seen that the fluorescence intensity of dendritic silica / quantum dots / silica nanospheres is almost unchanged at a salt concentration of up to 1M NaCl. Figure 6 It can be seen that the fluorescence intensity of dendritic silica / quantum dots / silica nanospheres at different pH values remains above 90%. Figure 7 It can be seen that the change in fluorescence intensity of dendritic silica / quantum dots / silica nanospheres after storage for 30 days is negligible.
[0056] Example 2
[0057] (1) Dendritic mesoporous silica (dSiO) with a size of 360 nm 2 ) Synthesis of carrier
[0058] Weigh 68 mg of triethanolamine and dissolve it in 25 mL of deionized water, stir at 80 ° C for 30 min, then add 380 mg of hexadecyltrimethylammonium bromide (CTAB) and 268 mg of sodium salicylate (NaSaI), and continue to react at 80 ° C for 1.5 h. Then add 4 mL of tetraethyl orthosilicate (TEOS) to the solution, continue to react at 80 ° C for 3 h, and collect the precipitate by centrifugation with ethanol after the reaction. Use a mixed solution of 100 mL of hydrochloric acid / methanol (volume ratio of 1:1) for purification, stir at 60 ° C for 6 h, and repeat this step more than three times to remove excess template CTAB. Finally, centrifuge and purify with ethanol three times, centrifuge at 9000 rpm for 3 min, and disperse again in 100 mL of ethanol to prepare dendritic silica with a size of 360 nm.
[0059] (2) Surface thiolation treatment of dendritic mesoporous silica
[0060] 1 mL of 3-mercaptopropyltriethoxysilane (MPTMS) and 3 mL of ammonia solution (mass concentration of 25-28 wt%) were added to the ethanol solution of the dendritic mesoporous silica synthesized in step (1), and the mixture was slowly stirred at room temperature for 15 h. Finally, the mixture was centrifuged three times with ethanol and centrifuged at 8000 rpm for 5 min. The collected precipitate was dispersed in 50 mL of ethanol again to obtain thiol-functionalized dendritic silica (dSiO 2 -SH) template.
[0061] (3) Dendritic Silica / Quantum Dots (dSiO 2 Preparation of nanostructured QDs (nano / QDs) assemblies
[0062] The ethanol solution of the thiolated silica template was centrifuged at 8000 rpm for 5 min, the supernatant was discarded, the precipitate was dried and 15 mg was accurately weighed, 1 mL of purified CdSe / CdZnS quantum dot toluene solution was added (the purification agent used was a mixed solution of chloroform, acetone and methanol, the volume ratio was 1:1:1, and the quantum dot concentration was 20 mg / mL), and ultrasonication was performed for 10 min to obtain a homogeneous transparent solution. In this step, CdSe / CdZnS quantum dots were assembled in the pores of dendritic silica. The dendritic silica / quantum dots (dSiO 2 The precipitate was washed with chloroform to remove free quantum dots and dispersed again in 5 mL toluene solution for later use.
[0063] (4) Preparation of dendritic silica / quantum dots / silica (SQS) fluorescent nanospheres
[0064] dSiO 2 The organosilane-modified dendritic silica / quantum dots (dSiO 2 / QDs / MPTMS). The dSiO 2 / QDs / MPTMS was centrifuged and the precipitate was washed again with ethanol. Methods To grow a silica shell, the above precipitate was dispersed in 20 mL of ethanol and 150 μL of tetraethyl orthosilicate, 300 μL of ammonia water, and 300 μL of water were added, and stirred at room temperature for 30 h. The solution was centrifuged and washed with ethanol three times to obtain high-brightness dendritic silica / quantum dots / silica fluorescent nanospheres.
[0065] Example 3
[0066] (1) Dendritic mesoporous silica (dSiO) with a size of 120 nm 2 ) Synthesis of carrier
[0067] Weigh 68 mg of triethanolamine and dissolve it in 25 mL of deionized water. Stir at 80 ° C for 30 min, then add 380 mg of hexadecyltrimethylammonium bromide (CTAB) and 60 mg of sodium salicylate (NaSaI), and continue to react at 80 ° C for 1.5 h. Then add 4 mL of tetraethyl orthosilicate (TEOS) to the solution, continue to react at 80 ° C for 4 h, and collect the precipitate by centrifugation with ethanol after the reaction. Finally, purify it with a mixed solution of 100 mL of hydrochloric acid / methanol (volume ratio of 1:1), stir at 60 ° C for 6 h, and repeat this step three times to remove the excess template CTAB. Finally, purify it by centrifugation with ethanol three times and disperse it in 100 mL of ethanol to prepare dendritic silica with a size of 120 nm.
[0068] (2) Surface thiolation treatment of dendritic mesoporous silica
[0069] 1.5 mL of 3-mercaptopropyltriethoxysilane (MPTMS) and 3 mL of ammonia solution (mass concentration of 25-28 wt%) were added to the ethanol solution of dendritic mesoporous silica in step (1), and the mixture was slowly stirred at room temperature for 12 h. Finally, the mixture was centrifuged three times with ethanol at a speed of 8000 rpm for 5 min, and the precipitate was collected and dispersed again in 50 mL of ethanol.
[0070] (3) Dendritic Silica / Quantum Dots (dSiO 2 Preparation of nanostructured QDs (nano / QDs) assemblies
[0071] The ethanol solution of the thiolated silica template was centrifuged at 8000 rpm for 5 min, the supernatant was discarded, the precipitate was dried and 15 mg was accurately weighed, 1 mL of purified CdZnSeS / ZnS quantum dot chloroform solution was added (the purification agent used was a mixed solution of chloroform, acetone and methanol, the volume ratio was 1:1:1, and the quantum dot concentration was 15 mg / mL), and ultrasonicated for 10 min to obtain a homogeneous transparent solution. In this step, CdZnSeS / ZnS quantum dots were assembled in the pores of dendritic silica. The dendritic silica / quantum dot assembly was collected by centrifugation at 10000 rpm for 5 min. The precipitate was washed again with chloroform to remove free quantum dots and dispersed again in 5 mL of toluene solution for use.
[0072] (4) Preparation of dendritic silica / quantum dots / silica (SQS) fluorescent nanospheres
[0073] dSiO 2 The organosilane-modified dendritic silica / quantum dots (dSiO 2 / QDs / MPTMS). The dSiO 2 / QDs / MPTMS was centrifuged and the precipitate was washed again with ethanol. Methods To grow a silica shell, the above precipitate was dispersed in 20 mL of ethanol and 100 μL of tetraethyl orthosilicate, 200 μL of ammonia water, and 300 μL of water were added, and stirred at room temperature for 18 h. The solution was centrifuged and washed with ethanol three times to obtain high-brightness dendritic silica / quantum dots / silica fluorescent nanospheres.
[0074] Example 4
[0075] (1) Dendritic mesoporous silica (dSiO) with a size of 470 nm 2 ) Synthesis of carrier
[0076] Weigh 68 mg of triethanolamine and dissolve it in 25 mL of deionized water. Stir at 80 ° C for 30 min, then add 380 mg of hexadecyltrimethylammonium bromide (CTAB) and 420 mg of sodium salicylate (NaSaI) and continue to react at 80 ° C for 1 h. Then add 4 mL of tetraethyl orthosilicate (TEOS) to the solution and continue to react at 80 ° C for 2 h. After the reaction, collect the precipitate by centrifugation with ethanol. Finally, purify it with a mixed solution of 100 mL of hydrochloric acid / methanol (volume ratio of 1:1), stir at 60 ° C for 6 h, and repeat this step three times to remove the excess template CTAB. Finally, purify it by centrifugation with ethanol three times and disperse it in 100 mL of ethanol to prepare dendritic silica with a size of 470 nm.
[0077] (2) Surface thiolation treatment of dendritic mesoporous silica
[0078] Add 1 mL of 3-mercaptopropyltriethoxysilane (MPTMS) and 2.5 mL of ammonia solution (mass concentration of 25-28 wt%) to the ethanol solution of the dendritic mesoporous silica synthesized in step (1), stir slowly at room temperature for 24 h, and finally centrifuge with ethanol three times at 9000 rpm for 3 min, collect the precipitate and disperse it again in 50 mL of ethanol.
[0079] (3) Dendritic Silica / Quantum Dots (dSiO 2 Preparation of nanostructured QDs (nano / QDs) assemblies
[0080] The ethanol solution of the thiolated silica template was centrifuged at 9000 rpm for 3 min, the supernatant was discarded, the precipitate was dried and 15 mg was accurately weighed, 1 mL of purified InP / ZnSe / ZnS quantum dot toluene solution (the purifying agent was a mixed solution of octane and ethanol, the volume ratio was 1:2, and the quantum dot concentration was 15 mg / mL) was added, and a homogeneous transparent solution was obtained by ultrasonication for 10 min. In this step, InP / ZnSe / ZnS quantum dots were assembled in the pores of dendritic silica. The dendritic silica / quantum dot assembly was collected by centrifugation at 10000 rpm for 5 min. The precipitate was washed with chloroform to remove free quantum dots and dispersed again in 5 mL of toluene solution for use.
[0081] (4) Preparation of dendritic silica / quantum dots / silica (SQS) fluorescent nanospheres
[0082] dSiO 2 The organosilane-modified dendritic silica / quantum dots (dSiO 2 / QDs / MPTMS). The dSiO 2 / QDs / MPTMS was centrifuged and the precipitate was washed again with ethanol. Methods To grow a silica shell, the above precipitate was dispersed in 20 mL of ethanol and 200 μL of tetraethyl orthosilicate, 250 μL of ammonia water, and 300 μL of water were added, and stirred at room temperature for 36 h. The solution was centrifuged and washed with ethanol three times to obtain high-brightness dendritic silica / quantum dots / silica fluorescent nanospheres.
[0083] The dendritic silica / quantum dots / silicon dioxide fluorescent nanospheres prepared in Examples 2-4 have similar optical properties to the nanospheres prepared in Example 1.
[0084] The embodiments described above provide a detailed description of the technical solutions and beneficial effects of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements and equivalent substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing high-brightness quantum dot fluorescent microspheres based on a base catalysis strategy, characterized in that: The following steps are involved: (1) Preparation of thiol-modified dendritic mesoporous silica microspheres; (2) assembling the thiol-modified dendritic mesoporous silica microspheres with quantum dots to obtain a dendritic silica / quantum dot assembly; (3) adding 3-mercaptopropyltriethoxysilane to the dendritic silica / quantum dot assembly, and using an organic base as a base catalyst in a non-polar organic solvent to modify the dendritic silica / quantum dot assembly with an organic silane; (4) Through Methods A silica shell was grown on the surface of organosilane-modified dendritic silica / quantum dot assemblies to obtain high-brightness quantum dot fluorescent microspheres.
2. The method for preparing high-brightness quantum dot fluorescent microspheres based on base catalysis strategy according to claim 1, characterized in that: Step (1) comprises: preparing dendritic mesoporous silica by a template method, and then modifying the surface of the dendritic mesoporous silica with thiol groups to obtain thiol-modified dendritic mesoporous silica microspheres.
3. The method for preparing high-brightness quantum dot fluorescent microspheres based on base catalysis strategy according to claim 2, characterized in that: Step (1) comprises: (1-1) Using hexadecyltrimethylammonium bromide as a template, sodium salicylate as a structure directing agent, triethanolamine as a catalyst, and water as a solvent, stirring the reaction at 50-100° C. for 0.5-2 h, adding a silicon source and continuing to stir the reaction for 2-3.5 h to obtain dendritic mesoporous silica; (1-2) Add 3-mercaptopropyltriethoxysilane and an alkaline solution to the dendritic mesoporous silica, and stir the mixture to react at room temperature to obtain thiol-modified dendritic mesoporous silica microspheres.
4. The method for preparing high-brightness quantum dot fluorescent microspheres based on base catalysis strategy according to claim 1, characterized in that: The particle size of the thiol-modified dendritic mesoporous silica microspheres is 100-500nm.
5. The method for preparing high-brightness quantum dot fluorescent microspheres based on base catalysis strategy according to claim 1, characterized in that: In step (2), the mass ratio of the thiol-modified dendritic mesoporous silica microspheres to the quantum dots is 1:1-2.
6. The method for preparing high-brightness quantum dot fluorescent microspheres based on base catalysis strategy according to claim 1 or 5, characterized in that: The quantum dots are at least one of CdSe / CdS / ZnS, CdZnSeS / ZnS, CdSe / CdZnS, InP / ZnSe / ZnS, and CuInS2 / ZnS; the ligands on the surface of the quantum dots are at least one of oleic acid, decadecanoic acid, stearic acid, and n-dodecyl mercaptan.
7. The method for preparing high-brightness quantum dot fluorescent microspheres based on base catalysis strategy according to claim 1, characterized in that: In step (3), the non-polar organic solvent is at least one of toluene, chloroform, octane, and cyclohexane; and the organic base is at least one of tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, and hexamethonium hydroxide.
8. The method for preparing high-brightness quantum dot fluorescent microspheres based on base catalysis strategy according to claim 1, characterized in that: Step (4) comprises: adding a silicon source to the dispersion of the organosilane-modified dendritic silica / quantum dot assembly, stirring and reacting at room temperature for 18-36 hours under the action of an alkali catalyst to obtain high-brightness quantum dot fluorescent microspheres.
9. The method for preparing high-brightness quantum dot fluorescent microspheres based on base catalysis strategy according to claim 8, characterized in that: In step (4), the base catalyst is 25-28 wt % ammonia water; the silicon source is tetraethyl silicate; and the volume ratio of the silicon source to the base catalyst is 1:1-3.
10. A high brightness quantum dot fluorescent microsphere, characterized in that: The method is prepared by any one of claims 1 to 9.
Citation Information
Patent Citations
Simple preparation method for silica-coated quantum dots
CN110129025A
Preparation method for high-luminescence quantum-dot fluorescent microsphere on basis of affinity assembling
CN109705840A
High-brightness fluorescent microsphere based on quantum dot layer-by-layer affinity assembly and application thereof
CN114250071A
Preparation method of silicon dioxide coated quantum dots
CN115125004A
Ultra-stable high-brightness quantum dot fluorescent microsphere as well as preparation method and application thereof
CN115820242A